Розуміння прекрасного в «критиці здатності судження» Іммануїла Канта - Логвіненко, А. О. (ХНУРЕ, 2019)
According to the title, the article considers Kant’s view of the beautiful, which he calls the ritica of the beautiful. The beautiful is a reasonable subject, which is a form of disinterested and general admiring.